Productivity Dynamics in Iranian Rainbow Trout (Oncorhynchus Mykiss Walbaum) Aquaculture - Hassanpour, Behrooz (2010)
Iran is one of the most favourable zones for rainbow trout farming in the world. This country yields 9.6% of the world’s total production and the third largest producer of rainbow trout after Chile (28.7%) and Norway (12.7%) (FAO Fish-Statistics, 2009). Rainbow trout farming units have played a prominent role in the development of aquaculture industry in Iranian fishery sector. In Iran, increase in population, lack of protein products and increase in meat prices in recent years are some of the positive contributions to fish farming. Thus, the Iranian government must give more attention to develop fish farming and enhance productivity. The purpose of this study is to measure the total factor productivity (TFP) change and to decompose the TFP change into its components, namely; technical efficiency change (EFFCH) and technological change (TECHCH), as well as to ascertain the socio-economic/bio-technical factors that might have impact on the TFP index dynamics in trout aquaculture. In order to achieve the objectives, a non-parametric model based on the data envelopment analysis (DEA) method and the Malmquist measures were applied. In addition, pooled-tobit and pooled-logit estimators, which were adopted in the study, were used to examine the determinants of TFP growth and its components. The data and information were gathered from recorded secondary data by the Iranian Fisheries Organization (IFO) in the specified period. Panel data were analyzed, which consisted of 207 sampled rainbow trout farms in homogeneous areas in the country over a five-year period from 2003 to 2007 (a total of 1035 ponds). The variables in the DEA analysis were fish production, pond area, number of fry, flow rate, quantity of feed and number of labour. The study was conducted to investigate the effects of several socioeconomic/bio-technical factors (18 factors) on the TFP growth and its components. The results of this study revealed that the TFP growth of rainbow trout farming had an increasing trend from 2003 to 2007. It increased at an average annual rate of 3.7%. The EFFCH also increased from the period at an average annual rate of 9.3%, while the TECHCH decreased at an average annual negative rate of -5.2%. However, the technological progress (innovation or adoption of improved techniques) was absent and the technical efficiency change was found to be the sole factor that contributed to the TFP growth. The findings revealed that many trout farmers did not adopt the best available technology, but used older or conventional production techniques instead. Further analysis also revealed that there was a general consistency between the results of the factors affecting the TFP indices derived from the logit and tobit models. Based on the marginal effect analysis derived from the pooledtobit and pooled-logit regressions, the factors that mostly affected TFPCH positively were ranked, and these included suitability of water temperature (i.e. 13-18oC), extension workshop, fry supply in farm (hatchery unit inside the farm) and flow rate. On the other hand, the negative factors comprised the number of illiterate labour workers, the number of labourers with lower than diploma qualification and the mean weight of fry. Meanwhile, the factors that mostly affected EFFCH positively were the usage of river water and extension workshop. On the contrary, the negative factors included the usage of spring water, the insurance coverage and the number of labourers with educational background lower than the diploma level. Lastly, the factors that mostly affected TECHCH positively were water temperature, extension workshop and educational level of the manager. Conversely, the negative factors included the insurance coverage, pond size and being tenure of government such as public companies and cooperatives. On policy recommendation, the government intervention in providing more incentives in order to attract more foreign direct investments (FDIs) will promote the development of modern technologies and managerial knowhow in Iranian aquaculture industry. Furthermore, the current insurance policy in trout aquaculture industry has played a etrimental role on the TFP growth trend; hence, the government should replace it with a more appropriate instrument, such as non-cash payment instead of cash payment when production fails. Moreover, the future aquaculture planning should also include the rainbow trout hatchery unit inside the farms. On the other hand, the Iranian government should also encourage the trout farms to employ labour forces who are literate, possess higher than the high school diploma, as well as to supply a complete technical package for improving and regulating water temperature in the trout farms, which can be beneficial for enhancing the TFP growth. The promotional extension and training activities, such as extension workshops in aquaculture, can contribute to human resource development in the aquaculture sector, and consequently reduce the gap between the best trout farms and other trout farms. Such extension workshops for innovation improvement of targeted trout farms may accelerate the adoption of better technology.